Dinamika Lembaga Perlindungan Anak di Indonesia (1997-2016) - Zhiyah Zhulma Zain; Kurniawati; Abrar (Criksetra: Jurnal Pendidikan Sejarah, 2021)
Child protection institutions are the 'home' for every child's problems that should be protected by the state. Constitutionally, the strengthening of child protection is based on the Act on Child Protection in 2002. The problem in this research is how the initial process and dynamics faced by child protection institutions in Indonesia. This study aims to describe the birth and dynamics of child protection institutions in Indonesia (1997-2016). The method used is the historical method consisting of heuristics, source criticism, interpretation and historiography. The results of this study indicate that 1997 is considered a milestone for the birth of child protection institutions in Indonesia, namely the establishment of GNPA by Suharto. To fulfill legal legality, LPA was formed through the Ministry of Social Affairs. This institution changed its name to Komnas PA in 1999. Based on the 2002 Child Protection Act, the KPAI was formed. The name change of child protection institutions in Indonesia since 1997-2002 is one of the efforts to legalize child protection institutions. Various problems regarding children are one of the dynamics that characterize child protection institutions in Indonesia.